An ontology based approach to teach computational thinking - Araújo, Cristiana (2019)
This paper is focused on the teaching/learning process of Computational Thinking at primary and secondary schools. It is generally accepted that Programming is a complex task that requires a long learning process. Theoretical knowledge about fundamentals on algorithms and data structures, as well as, on programming languages are required but are not enough; practicing a lot is also necessary. However, teaching Computer Programming is a hard job, most of the times unsuccessful. To overcome all the difficulties, felt by teachers and students, an increasingly bigger community of researchers in Computer Science is defending the importance of teaching Computational Thinking to young students to train them, since very earlier, in logic and abstract reasoning for problem solving. Our starting point to approach this topic relies on the use of an Ontology (OntoCnE) that describes in detail the concepts 'Computational Thinking' and 'Programming', and maps those concepts to different education levels, starting with the first year. We believe that a person just acquires a new way of thinking, or a new way of behaving, if he is trained with the appropriate learning resources. So a main investment to educate people in Computational Thinking is on the choice/creation of those convenient resources. In particular we intended to investigate the impact of Augmented Reality in the usefulness of the referred resources. In that direction we will also discuss the development of a Web Platform to help on collecting and classifying (according to the referred ontology) learning resources to be used by teachers in computing classes. On the other hand, the platform will help on the retrieval, from that repository, of the most adequate resources to teach a specific subject to a specific level.